Market Making in the Options Markets and the Costs of Discrete Hedge Rebalancing - JAMESON, MEL; WILHELM, WILLIAM (Journal of Finance, 1992)
ABSTRACT In this paper we provide empirical evidence consistent with the hypothesis that options market makers face risks in managing inventory that are unique to the options markets. In particular, we show that risks associated with the inability to rebalance an option position continuously and uncertainty about the return volatility of the underlying stock each account for a statistically and economically significant proportion of the bid‐ask spreads quoted for a sample of Chicago Board Options Exchange options.